2018
DOI: 10.1371/journal.pone.0196590
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome reprogramming of resistant and susceptible peach genotypes during Xanthomonas arboricola pv. pruni early leaf infection

Abstract: Bacterial spot caused by Xanthomonas arboricola pv. pruni (Xap) is a major threat to Prunus species worldwide. The molecular mechanisms of peach resistance to Xap during early leaf infection were investigated by RNA-Seq analysis of two Prunus persica cultivars, ‘Redkist’ (resistant), and ‘JH Hale’ (susceptible) at 30 minutes, 1 and 3 hours-post-infection (hpi). Both cultivars exhibited extensive modulation of gene expression at 30 mpi, which reduced significantly at 1 hpi, increasing again at 3 hpi. Overall, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 78 publications
1
19
0
Order By: Relevance
“…The speci c suppression of photosynthesis, sugar metabolism and other chloroplast-associated genes observed in BAT93 re ects a rather classical defense response. Indeed, similar trends have been described using transcriptomics in different interactions between plants and bacteria [91][92][93][94] and integration of transcriptomic data from different pathosystems led to the hypothesis that suppression of photosynthesis is part of the plant adaptive immunity [95]. In addition, several studies have shown that incompatible interaction is linked to a decrease in photosynthetic activity [96][97][98][99] and that inhibition of photosynthesis often leads to the accumulation of reactive oxygen species [100].…”
Section: Discussionmentioning
confidence: 66%
“…The speci c suppression of photosynthesis, sugar metabolism and other chloroplast-associated genes observed in BAT93 re ects a rather classical defense response. Indeed, similar trends have been described using transcriptomics in different interactions between plants and bacteria [91][92][93][94] and integration of transcriptomic data from different pathosystems led to the hypothesis that suppression of photosynthesis is part of the plant adaptive immunity [95]. In addition, several studies have shown that incompatible interaction is linked to a decrease in photosynthetic activity [96][97][98][99] and that inhibition of photosynthesis often leads to the accumulation of reactive oxygen species [100].…”
Section: Discussionmentioning
confidence: 66%
“…The specific suppression of photosynthesis, sugar metabolism and other chloroplast-associated genes observed in BAT93 reflects a rather classical defense response. Indeed, similar trends have been described using transcriptomics in different interactions between plants and bacteria [83][84][85], and integration of transcriptomic data from different pathosystems led to the hypothesis that suppression of photosynthesis is part of the plant adaptive immunity [86]. In addition, several studies have shown that incompatible interaction is linked to a decrease in photosynthetic activity [87][88][89][90] and that inhibition of photosynthesis often leads to the accumulation of reactive oxygen species [91].…”
Section: Discussionmentioning
confidence: 67%
“…Additionally, we observed that 83 genes 505 were upregulated at 48 hai. Downregulation of genes associated with photosynthesis is a 506 general phenomenon that can support defense response initiation against biotic stresses 507 [113,114], which is evidenced in RNA-Seq of infected leaves of other species [34,37,100]. 508 Our data shows that this repression occurred for a majority of genes in the first 12 509 hours after inoculation with P.kuehnii, later restored to basal expression levels at 48 hai 510 (Fig 1-C).…”
mentioning
confidence: 67%
“…Furthermore, this kind 462 of response can be delayed in compatible interactions [107]. Hence, high expression of 463 PAL-encoding genes is a common attribute of resistant cultivars [31,34], including 464 those of sugarcane [39,40,42]. In the P. kuehnii pathosystem the five DEGs annotated 465 as PAL were repressed at 12 hai, but three of them were upregulated in the next hours, 466 returning to the basal level at 5 dai (Fig 2-C).…”
mentioning
confidence: 98%
See 1 more Smart Citation